Design sensitivities from public expression practices with non-digital displays - Coutinho, José Pedro Lima Magriço (2015)
Digital public displays can have a huge potential as a communication medium for individual creativity and self-expression. However, opening public displays to usergenerated content and personalisation requires content publication practices that people may easily understand and appropriate according to their communication goals. This is crucial for both the individuals exposing their media on the displays and for the owners of those displays. In this work, we study a range of public expression practices that are already in common use. Although they rely on some form of non-digital display, they can provide important design inspirations for situated digital displays. Based on the analysis of descriptions of those practices and semistructured interviews with 25 interviewees, we identify a range of design sensitivities arranged around 3 fundamental themes: authorship; appropriateness; and collaboration. These should inform the design of novel approaches for enabling digital displays to become a new medium for public expression.